Exploring the Role of Problem-Based Learning in Fostering Social Literacy, Critical Thinking, and Religiosity in Social Studies Education - Sulfiani; Amriani; Muhammad Aqsa; Mehmet Cuma Tahiroglu (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to examine in depth the implementation of Problem-Based Learning (PBL) in social studies education and its impact on the development of social literacy, critical thinking, and religiosity among junior high school students. The study employed a qualitative case study design conducted over a three-month period. Participants were selected through purposive sampling and consisted of social studies teachers and eighth-grade students. Data were collected through in-depth interviews, participant observation, and document analysis. The data were analyzed using thematic coding to identify recurring patterns and core themes. The analysis revealed four major themes: (1) the implementation of student-centered learning through group discussions, case studies, and reflective activities; (2) the integration of social care and responsibility values within real-life social contexts; (3) positive learning outcomes reflected in improved social literacy and critical thinking skills; and (4) learning constraints, particularly limited instructional time and uneven student participation. The findings indicate that contextual learning media such as presentations, videos, and authentic social issues effectively enhance students’ cognitive engagement and strengthen their religiosity in both affective and behavioral dimensions. However, structural limitations, including restricted technological access and limited instructional time, remain significant challenges. This study contributes to the growing discourse on integrative social studies pedagogy by demonstrating that PBL can simultaneously foster social literacy, critical thinking, and religiosity within a unified instructional framework. It also offers practical implications for curriculum adaptation, systematic teacher training, and the development of collaborative learning environments to optimize students’ holistic development.